Skill and Deskilling in Two Automotive Assembly Plants in South Africa - Ngcwangu, Siphelo (Qualitative Sociology Review, 2023)
This article presents research on skills development and workplace change complexities within two automotive assembly plants in Pretoria, South Africa. Auto assembly companies are also termed Original Equipment Manufacturers (OEMs). Since 1995, South African OEMs have become fully integrated into the global networks of their foreign parent companies. As South Africa’s leading manufacturing sector, the automotive industry’s increasing importance is reflected in its exports, investments, and contribution to the country’s gross domestic product. The two companies are global multinationals situated in one of South Africa’s most globally integrated sectors that have undergone significant mechanization and automation since the 1990s. Therefore, these companies present a relevant site for studying changes in the labor process and the tendencies of deskilling in these workplace environments. The research is based on a qualitative research design that used semi-structured interviews with workers, supervisors, and managers across two plants that assemble motor vehicles in South Africa. The objective of the research was to understand the nature of changes to workplace production methods that influence the character of skills amongst the workforce. This paper studies workers’ experiences on how changes in work processes have impacted their work skills and contributed to the processes of deskilling. Present studies of skills in South Africa have prioritized large-scale labor market aggregate data analysis or reforms in education and training policies of the state. This paper brings a perspective on the labor process changes that are informed by concrete analysis of the production process and how technological changes shape the character of skills formation within automotive assembly plants. The value of such an approach is that it brings to the discussion of technology and workplace change a more specific set of experiences that transcends the often speculative and mythical discussion about the impact of technology on work. This article highlights the importance of understanding workers’ voices, shift supervisors, and managers on the contested nature of skills development within capitalist enterprises. The findings illustrate the contradictory nature of technological change and skills development. This is shown by discussing the following themes that emerged from the findings: 1) worker responses to the introduction of robots in the workplace environment, 2) the deskilling challenge on the two plants, and 3) grappling with the turnover times of capitalist production. I conclude the paper by revisiting the key findings of the research and showing the implications for future studies of deskilling in contemporary capitalist enterprises. The significance of these findings ultimately points to the importance of locating labor processes and deskilling in the context of the political economy of the capitalist mode of production and how it is reshaping the content of work in modern automotive assembly plants.